PENGARUH PELAPORAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA KEUANGAN DAN MANAJEMEN LABA (Studi pada Perusahaan Pertambangan Sub Sektor Minyak dan Gas Bumi yang Terdaftar di BEI tahun 2012-2018) - Agtia Intan Herdita (Jurnal Ilmiah Mahasiswa FEB, 2019)
The requirements for companies to compete well and to survive in the face of any circumstances are recently increasing. One of the requirements is the necessity to report their CSR. This study aims to provide empirical evidences concerning the influence of Corporate Social Responsibility (CSR) reporting on corporate financial performance and earnings management. The independent variable used in this study is Corporate Social Responsibility (CSR) report, measured using GRI-G4. The dependent variables are financial performance, proxied by ROA and ROE, and earnings management, proxied by discretionary accruals. Using purposive sampling, 44 annual financial statements that meet the criteria were selected as the sample. The results of the simple linear regression analysis indicate that Corporate Social Responsibility report positively affects financial performance that is proxied by ROA, but it has no effect on earnings management and financial performance that is proxied by ROE. Keywords: Corporate Social Responsibility reporting, financial performance, ROA, ROE, earnings management